Effect of (TOC) and Internal Auditing (AI) on Enhancing the Sustainable Performance of Industry: An Empirical Study - Abdulqudoos Hussein Mohammed (Academia Open, 2026)
General Background Sustainable performance has become a central concern for organizations seeking to balance economic, environmental, and social objectives. Specific Background Prior studies emphasize sustainability performance measurement systems and managerial frameworks, yet operational limitations often hinder their practical application. Knowledge Gap Limited attention has been given to integrating sustainability performance concepts with theory of constraints to explain performance limitations systematically. Aims This article aims to analyze sustainable performance by combining sustainability management perspectives with theory of constraints as an analytical framework. Results The analysis shows that organizational constraints play a critical role in shaping sustainability performance outcomes and that structured performance management systems can help identify and address these constraints. Novelty The novelty of this study lies in linking sustainability performance measurement with constraint-based operational thinking within a unified conceptual framework. Implications The findings provide insights for managers and policymakers to better align sustainability goals with operational decision-making processes. Highlights: Organizational constraints are central determinants of sustainability-oriented outcomes Sustainability performance systems benefit from integration with operational frameworks Constraint-based analysis supports balanced economic and social decision-making Keywords: Sustainable Performance, Theory of Constraints, Sustainability Management, Performance Measurement, Organizational Constraints